Systemic potency of fluticasone in asthma. Issue 3 (5th March 2020) - Lipworth, Brian; Kuo, Chris RuiWen; Chan, Rory
We read with interest the data from Maijers et al. [1], suggesting that in a post hoc analysis of trials in oral corticosteroid (OC)-dependent asthma, the majority of the OC-sparing effects of high-dose inhaled corticosteroids are due to their systemic effects. The meta-regression estimates showed a prednisone (Pred) decrease of 4.9 mg per 1.0 mg increase in fluticasone propionate (FP) dose. This was based on the premise from an analysis of two studies where 1.0 mg FP was equivalent to 5.0 mg Pred for cortisol suppression, although this was only calculated in reference to a 10 mg dose of Pred. A ratio of 1.02 was then inferred for the proportion of the OC-sparing effect due to systemic absorption of FP. Use of high dose fluticasone propionate requires similar considerations as starting maintenance low dose prednisone http://bit.ly/3aLXcjO